2013
DOI: 10.1111/ajt.12035
|View full text |Cite
|
Sign up to set email alerts
|

Conversion From Twice-Daily Tacrolimus to Once-Daily Extended Release Tacrolimus (LCPT): The Phase III Randomized MELT Trial

Abstract: Phase III noninferiority trial examining efficacy and safety of converting stable renal transplant recipients from twice-daily tacrolimus to a novel extended-release once-daily tacrolimus formulation (LCPT) with a controlled agglomeration technology. Controls maintained tacrolimus twice daily. The primary efficacy endpoint was proportion of patients with efficacy failures (death, graft failure, locally read biopsy-proven acute rejection [BPAR], or loss to follow-up) within 12 months. Starting LCPT dose was 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
84
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 19 publications
10
84
0
4
Order By: Relevance
“…Aside from the direct vascular effect on renal blood flow, the potential direct nephrotoxic effects of CNI agents remain an active area of debate and research (21). To address these issues of toxicity and side effect profiles (including post-transplant diabetes), alternative formulations of tacrolimus (extended release) as well as the novel CNI voclosporin have been developed and are approved or in late-phase clinical trials in transplantation (22)(23)(24).…”
Section: Agents Targeting Signalmentioning
confidence: 99%
“…Aside from the direct vascular effect on renal blood flow, the potential direct nephrotoxic effects of CNI agents remain an active area of debate and research (21). To address these issues of toxicity and side effect profiles (including post-transplant diabetes), alternative formulations of tacrolimus (extended release) as well as the novel CNI voclosporin have been developed and are approved or in late-phase clinical trials in transplantation (22)(23)(24).…”
Section: Agents Targeting Signalmentioning
confidence: 99%
“…16 The efficacy of LCP-Tacro has been shown to be noninferior in comparison with Prograf in kidney transplantation. 17 The present study compared the pharmacokinetic (PK) and safety profile of once daily LCP-Tacro tablets to that of twice daily Prograf capsules in stable liver transplant recipients. Long-term safety and tolerability were evaluated during an open-label, 50-week extension phase.…”
mentioning
confidence: 99%
“…The average trough concentration did not differ between the 2 treatments at 12 months (LCP-TAC, 5.19 vs TAC 5.07 ng/mL). However, the cumulative dose at 12 months was significantly lower (4.5 vs 4.8 for QD in BID; P < .001) [15].…”
Section: Discussionmentioning
confidence: 86%
“…In a study by Bunnapradist et al [15], the authors, on 162 stable KTx patients, found evidence of graft protection after 1 year of treatment with either TAC or LCP-TAC. The average trough concentration did not differ between the 2 treatments at 12 months (LCP-TAC, 5.19 vs TAC 5.07 ng/mL).…”
Section: Discussionmentioning
confidence: 99%